Transversal and longitudinal gluon spectral functions from twisted mass lattice QCD with Nf=2+1+1 flavors - Ilgenfritz, Ernst-Michael; Pawlowski, Jan M.; Rothkopf, Alexander (Physics of particles and nuclei letters, 2018)
I report on the first application of a novel, generalized Bayesian reconstruction (BR) method for spectral functions to the characterization of QCD constituents. These spectral functions find applications in off-shell kinetics of the quark-gluon plasma and in calculations of transport coefficients. The new BR method is applied to Euclidean propagator data, obtained in Landau gauge on lattices with Nf = 2 + 1 + 1 dynamical flavors by the “twisted mass at finite temperature” (tmfT) collaboration. The deployed reconstruction method is designed for spectral functions that can exhibit positivity violation (opposed to that of hadronic bound states). The transversal and longitudinal gluon spectral functions show a robust structure composed of quasiparticle peak and a negative trough. Characteristic differences between the hadronic and the plasma phase and between the two channels become visible. We obtain the temperature dependence of the transversal and longitudinal gluon masses.
Im Titel ist "f" bei Nf tiefgestellt
Gesehen am 01.12.2020